Diseño de material didáctico en el estudio de las leyes de reflexión y refracción de la luz. - Espín Freire, Sofía de los Ángeles (2024)
The present research, Design of Didactic Material for the Study of the Laws of Reflection and Refraction of Light, aims to develop instructional materials for these fundamental concepts in optics. This initiative resulted in the creation of both the materials and a comprehensive didactic guide for students enrolled in the Optics course as part of the Pedagogy of Experimental Sciences with Emphasis in Mathematics and Physics program.The research seeks to elucidate the physical principles governing reflection and refraction through engaging activities that promote meaningful and effective learning, utilizing specially designed instructional materials. The study employs a non-experimental design with a quantitative, field-based, cross-sectional approach at a descriptive-propositional level. Data collection was conducted using surveys, with a questionnaire administered to eighth-semester students who participated in the study. The collected data were processed using descriptive statistics in RStudio software. Analysis of the results highlighted specific challenges students faced in understanding the laws of reflection and refraction, prompting the development of a teaching guide tailored to enhance the educational process effectively and practically. In conclusion, it is recommended that the designed didactic materials be implemented in the classroom. Additionally, evaluations should be conducted at both the beginning and end of the course to measure students' progress and improvements in their understanding of the subject matter